PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XIF SMAN 1 SUNGAI LIMAU - Wulandari, Khairani (Departemen Matematika, 2024)
Understanding mathematical concepts is necessary to hone other skills. In reality, that understanding is still very lacking. The results of the first test given to the students of class XE at SMAN 1 Sungai Limau in the 2023/2024 academic year support this. One approach to better understand this is by implementing the cooperative learning model Think Pair Share. (TPS). The type of research is quasi-experimental. The sampling technique uses simple random sampling. Higher conceptual understanding is shown in students who learn with TPS compared to students who use the conventional approach (P-Value = 0.000 < α = 0.05).Keywords. – Understanding of Mathematical Concept, Think Pair Share